IGLC1 is an independent prognostic marker and potent therapeutic target in osteosarcoma - Zhenjie Wu; Xinlian Xie; Guangfu Shi; Kebin Ning; Jinmin Zhao (Discover Oncology)
Abstract Background Immunoglobulin lambda constant 1 (IGLC1) has been implicated in cancer progression, but its role in osteosarcoma remains unclear. This study endeavored to explore the levels of IGLC1 expression, its implications for patient prognosis, and its functional impact within the context of osteosarcoma. Methods IGLC1 expression was analyzed in 108 osteosarcoma tissues and 42 non-neoplastic bone samples. Associations with clinicopathological features were evaluated using chi-square tests. Prognostic value was assessed via univariate and multivariate Cox regression analyses. Functional assays, including CCK-8, colony formation, transwell migration, wound healing, and invasion assays, were conducted following IGLC1 knockdown in MG-63 and 143B cell lines. Results High IGLC1 expression was observed in 55.6% of osteosarcoma cases, significantly higher than in non-neoplastic bone tissues (P < 0.05), and was associated with larger tumor size, high Lactate Dehydrogenase (LDH) and poor chemotherapy response (P < 0.05). Univariate analysis identified high IGLC1 expression (HR = 3.028, 95% CI = 1.687–5.437, P < 0.001) and elevated LDH levels (HR = 2.793, 95% CI = 1.630–4.789, P < 0.001) as significant prognostic factors for poor overall survival. Multivariate analysis confirmed both high IGLC1 expression (HR = 2.336, 95% CI = 1.214–4.495, P = 0.011) and elevated LDH levels (HR = 1.950, 95% CI = 1.062–3.579, P = 0.031) as independent predictors of poor overall survival. Functional studies revealed that IGLC1 knockdown significantly inhibited osteosarcoma cell proliferation, colony formation, migration, and invasion. Conclusion IGLC1 is a novel independent prognostic marker that promotes tumor progression in osteosarcoma. Therapeutic strategies targeting IGLC1, such as inhibiting its expression or blocking its downstream signaling pathways, may provide innovative approaches for osteosarcoma treatment.